Highly Efficient, Surface Ligand Modified Quantum Dot Light‐Emitting Diodes Driven by Type‐Controllable MoTe2 Thin Film Transistors via Electron Charge Enhancer. (26th July 2021) - Baek, Geun Woo; Seo, Seung Gi; Hahm, Donghyo; Bae, Wan Ki; Kwak, Jeonghun; Jin, Sung Hun
Abstract: The development of transition metal dichalcogenides (TMDCs) and quantum dots (QDs) as the promising semiconductor and emitter is carried out in diverse applications. Despite superb research progress, study of emerging devices incorporated with TMDC thin film transistors (TFTs) and quantum dot light‐emitting diodes (QLEDs) is rarely reported. Herein, the QLEDs operation controlled by p (or n‐type) molybdenum ditelluride (MoTe2 ) TFTs with the realization of complementary type transistor is first demonstrated. In this study, molecular doping by poly‐L‐lysine (PLL) is adopted for a type conversion of MoTe2 TFTs and surface ligand modification is utilized for improvement of QLED performance. As a result, the PLL treatment achieves the outstanding type conversion of MoTe2 TFTs without any degradation of electrical properties, leading to securing reliable n or p‐type devices, thus, availability of complementary circuits. Furthermore, ligand modified QDs capped with octylamine result in balanced electron/hole injection in QLEDs, yielding improved current efficiency (ηA = 13.9 cd A −1 ) and longer lifetimes ( T 50 = 66 h at L 0 = 3000 cd m −2 ). Lastly, MoTe2 TFTs demonstrate their capabilities to drive the QLEDs for the envisioned application including display backplane transistor with decent switching properties, immunity for generation of photocurrent, and operation stability. Abstract : In this study, the operation of quantum dot light‐emitting diodes (QLEDs) display driven by molybdenum ditelluride thin film transistors (MoTe2 TFTs) is demonstrated. With achievement of complementary type MoTe2 TFTs by molecular doping, immunity for photoresponse in MoTe2 TFTs, performance improvement of QLEDs via ligand modification, and driving capabilities of MoTe2 TFTs for the operation of QLEDs are successfully substantiated.